High doses of lidocaine as a constant rate infusion in propofol/ fentanyl anaesthetized sheep: cardiorespiratory effects - Ewaldo de Mattos-Junior (Semina: Ciências Agrárias, 2013)
The aim of this study was to investigate the cardiorespiratory and anesthetic-sparing effects of a high- dose CRI of lidocaine (200 μg/kg/min) administered with a propofol/fentanyl regimen to sheep. Twelve adult, castrated male sheep (BW= 32.1 ± 4.9 kg), were used in a prospective, randomized clinical trial. All animals were premedicated with xylazine (0.05 mg/kg, i.m.). Animals in the GPF group were induced with propofol (3 mg/kg) and fentanyl (2.5 μg/kg) intravenously, and anesthesia was maintained with a CRI of propofol (500 μg/kg/min) and fentanyl (0.15 μg/kg/min). In the GPFL group, animals were induced with propofol (3 mg/kg), fentanyl (2.5 μg/kg) and lidocaine (2.5 mg/kg) intravenously, and anesthesia was maintained with a CRI of propofol (500 μg/kg/min), fentanyl (0.15 μg/kg/min) and lidocaine (200 μg/kg/min); after ten minutes of anesthesia, the propofol dose was reduced by 25% (from 500 μg/kg/min to 375 μg/kg/min). Cardiorespiratory parameters were recorded from 15 minutes after preanesthetic medication administration (T0) to the end of the anesthetic procedure (T7). The time points were as follows: T0 – 15 minutes after preanesthetic medication administration; T1 – after anesthesia induction and orotracheal intubation; T2 – 15 minutes of anesthesia; T3 – during traction on the liver; T4 – during bowel clamping; T5 – during muscle suture; T6 – at the end of skin suture; and T7 – 15 minutes after the end of anesthesia. Apnea was present in all animals during anesthesia induction and required mechanical ventilation. There was no statistical difference in HR and MAP between any time points compared to the baseline value (p > 0.05); MAP was lower in the GPF group (p < 0.05) at time T6. In conclusion, this dose of lidocaine was sufficient to reduce the propofol requirement by 25%. A high-dose CRI of lidocaine in combination with a propofol/fentanyl regmine did not promote significant cardiovascular changes and was effective in reducing the propofol dose by 25%.